When Girl Become Wives: The Portrait of Underage Marriage in Indonesia - Fadhilah Rizky Afriani Putri (The Indonesian Journal of International Clinical Legal Education, 2020)
In Indonesia underage marriage is still prevalent in several regions. Underage marriage occurs due to several factors. The factor that often occurs is because a woman's family is not capable, lacks knowledge, and considers women to be only dependent on men. This underage marriage causes a lot of divorce, domestic violence because of the age that is immature to get married so that it cannot solve household problems properly and rationally. The most perpetrators of underage marriage are women. This underage marriage also makes women lose the right to education. Because if women marriage, they have to be a wife and a mother, education must be abandoned. So that girls do not get their rights to education. So from this journal will discuss the protection of minors in young age marriage. Especially in the education rights of married girls.